1995
DOI: 10.1086/647028
|View full text |Cite|
|
Sign up to set email alerts
|

Controlling Vancomycin-Resistant Enterococci

Abstract: After controlling an epidemic of vanB-type vancomycin-resistant Enterococcus faecium (VRE), we contained a subsequent vanA E faecium outbreak by using prospective laboratory-based surveillance, placing patients with VRE in private rooms, requiring the use of both gowns and gloves by all personnel entering the patients' rooms, and conducting prevalence surveys of patients on affected wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 5 publications
1
78
0
1
Order By: Relevance
“…20 -23 In an MRSA or VRE epidemic situation, widespread contamination of inanimate surfaces in rooms of affected patients has been documented. 13,17 Rutala and colleagues 29 showed that during an MRSA epidemic in a burn unit, MRSA comprised 16, 31 and 40% of all bacteria growth from air, elevated surfaces and floors, respectively. However, interestingly, investigations into epidemics have not confirmed that patients were infected due to the surrounding environmental contamination.…”
Section: Discussionmentioning
confidence: 99%
“…20 -23 In an MRSA or VRE epidemic situation, widespread contamination of inanimate surfaces in rooms of affected patients has been documented. 13,17 Rutala and colleagues 29 showed that during an MRSA epidemic in a burn unit, MRSA comprised 16, 31 and 40% of all bacteria growth from air, elevated surfaces and floors, respectively. However, interestingly, investigations into epidemics have not confirmed that patients were infected due to the surrounding environmental contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Reported incidence of VRE infections is believed to grossly underestimate the true prevalence because many patients act as carriers of enterococci (7)(8)(9). Molecular epidemiological studies of early endemic infections suggested clonal outbreaks (8).…”
mentioning
confidence: 99%
“…Reported incidence of VRE infections is believed to grossly underestimate the true prevalence because many patients act as carriers of enterococci (7)(8)(9). Molecular epidemiological studies of early endemic infections suggested clonal outbreaks (8). More recent ICU studies have appeared to involve more than one clone, perhaps demonstrating frequent introductions from other parts of the hospital (9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the usefulness of contact precautions and isolation as part of a concerted infection control effort to control the spread of GRE during a clonal outbreak has been reported by many centers over the past several years, the specific contribution of contact precautions is unknown [34,44,45]. Furthermore, the usefulness of contact precautions for GRE-colonized or -infected patients once GRE becomes endemic is unknown.…”
Section: Control Of Glycopeptide-resistant Enterococcimentioning
confidence: 99%